The Effects of Executive and Company Characteristics on Tax Aggressiveness - Dewi, Kristina Surya; Yasa, Gerianta Wirawan (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020), 2020)
Tax aggressiveness is the act of manipulating profits carried out through tax planning both legal and illegal. Based on agency theory, differences in interests between companies and the government calculating with taxes will encourage companies to maximize their interests by carrying out tax aggressiveness. The aim of this study is to determine and obtain empirical on the effect of executive characteristics, profitability, leverage, capital intensity, and company size on tax aggressiveness. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018, because the Indonesian economy was started to recover and it also impact on tax revenues. The research sample was selected using purposive sampling technique and obtained 70 mannufacturing companies, so the number of observation in the study was 210 observation. Data analysis technique used is multiple linear regression analysis.The results of this study, showed that executive characteristics, profitability, and company size had a positive effect on tax aggressiveness. While leverage and capital intensity had negative effect on tax aggressiveness. Keywords: Tax aggressiveness; executive characteristics; profitability; leverage; capital intensity; company size.